2022
DOI: 10.1101/2022.05.10.491356
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Novel tumorigenic FOXM1-PTAFR-PTAF axis revealed by multi-omic profiling in TP53/CDKN2A-double knockout human gastroesophageal junction organoid model

Abstract: Inactivation of the tumor suppressor genes TP53 and CDKN2A occurs early during gastroesophageal junction (GEJ) tumorigenesis. However, due to a paucity of GEJ-specific disease models, cancer-promoting consequences of TP53 and CDKN2A inactivation at the GEJ have been incompletely characterized. Here we report the development of the first wild-type primary human GEJ organoid model, as well as a CRISPR-edited transformed GEJ organoid model. CRISPR/Cas9 engineering to inactivate TP53 and CDKN2A (TP53/CDKN2AKO) in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 69 publications
(62 reference statements)
0
1
0
Order By: Relevance
“…High-throughput chemical screening identified that ARID1A-deficient gastric organoids were uniquely vulnerable to inhibition of BIRC5/survivin [ 18 ]. Our group recently [ 27 ] generated a novel model based on wild-type and TP53/CDKN2A dual-knockout (DKO) human normal gastroesophageal junction (GEJ)-derived organoids edited by using CRISPR/Cas9. DKO organoids grew faster, became larger, and exhibited de novo intestinal, metaplastic, and dysplastic morphology.…”
Section: Pdo Pharmacogenomics Linking Driver Mutations To Therapeutic...mentioning
confidence: 99%
“…High-throughput chemical screening identified that ARID1A-deficient gastric organoids were uniquely vulnerable to inhibition of BIRC5/survivin [ 18 ]. Our group recently [ 27 ] generated a novel model based on wild-type and TP53/CDKN2A dual-knockout (DKO) human normal gastroesophageal junction (GEJ)-derived organoids edited by using CRISPR/Cas9. DKO organoids grew faster, became larger, and exhibited de novo intestinal, metaplastic, and dysplastic morphology.…”
Section: Pdo Pharmacogenomics Linking Driver Mutations To Therapeutic...mentioning
confidence: 99%